2020
DOI: 10.1159/000506425
|View full text |Cite
|
Sign up to set email alerts
|

Altered Epidermal Permeability Barrier Function in the Uninvolved Skin Supports a Role of Epidermal Dysfunction in the Pathogenesis of Occupational Hand Eczema

Abstract: Although a compromised epidermal permeability barrier can contribute to the development of contact dermatitis, whether subjects with hand eczema display abnormalities in baseline epidermal permeability barrier function in their uninvolved skin remains unknown. The aim of the present study was to assess epidermal permeability barrier function in subjects with and without hand eczema in clothing manufacturers. Upon approval by the institutional review board, volunteers were recruited from clothing manufacturers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…This is possibly due to an increase in the skin pH of health workers' hands due to the longterm use of latex-based latex gloves. 21 However, Wang et al stated that an increase in pH was more common in occupational hand eczema (p < 0.01) 21,22 , though our results showed that the pH value was not correlated with the incidence of hand eczema (r=0.042, p=0.696). The correlation between skin pH values and the incidence of hand eczema, which was not significant, could be caused by the frequent use of hand sanitizer or hand rub on health workers who contain alcohol.…”
Section: Discussioncontrasting
confidence: 75%
“…This is possibly due to an increase in the skin pH of health workers' hands due to the longterm use of latex-based latex gloves. 21 However, Wang et al stated that an increase in pH was more common in occupational hand eczema (p < 0.01) 21,22 , though our results showed that the pH value was not correlated with the incidence of hand eczema (r=0.042, p=0.696). The correlation between skin pH values and the incidence of hand eczema, which was not significant, could be caused by the frequent use of hand sanitizer or hand rub on health workers who contain alcohol.…”
Section: Discussioncontrasting
confidence: 75%
“…15,21,24 Atopic hand eczema, like other atopic conditions, presents with a Th2/ Th22 immune profile, in conjunction with endogenous factors such as tight junction defects and an increase in transepidermal water loss (TEWL), thereby compromising the integrity of the epidermal barrier. 1,[25][26][27][28] Atopic hand eczema lesions are characterized by increased Th2 activation and production of IL-4, IL-13, IL-31, CCL17, CCL18, and CCL22, and T-cell activation that produces IL-22. IL-4/IL-13 also induce increased IgE synthesis, which characterizes many CHE cases.…”
Section: Chronic Hand Eczema Prevalence and Clinical Presentationmentioning
confidence: 99%
“… 16 In the NL skin transcriptome of VHE, no significant differences with healthy skin were found, which is striking as it has been hypothesized that a primary dysfunctional epidermal barrier is one of the key pathways for developing HE. 27 , 59 , 60 , 61 , 62…”
Section: Discussionmentioning
confidence: 99%
“…16 In the NL skin transcriptome of VHE, no significant differences with healthy skin were found, which is striking as it has been hypothesized that a primary dysfunctional epidermal barrier is one of the key pathways for developing HE. 27,[59][60][61][62] One of the limitations of our study is the small sample size of ten HE patients vs. ten healthy controls. Secondly, it is important to note that we used stringent criteria for the RNA-seq data as presented in Figure 2 (fold-change ≤−3 or ≥3, >500 average normalized counts).…”
Section: F I G U R E 1 Multivariate Gene Expression Analysis By Pcamentioning
confidence: 99%